(untitled) (International Journal of Physiotherapy, 2019)
Background: In today’s world, the application of information and communication technology is rapidly expanding and has transformed all aspects of life, including education, into its different forms, to the point where knowledge production is virtually impossible without the use of technology. On the other hand, the importance of its role in economic and social developments is increasing day by day. In recent years, we have seen the growth of the use of IT- technology, which initially served as an auxiliary tool and now as a factor in the development of education and treatment. So, this study aimed to investigate the shortening habilitation process of a patient using IT-based technology. Methods: The design for this study was a semi-experimental design with two groups of the experimental and control group. The study participants were elderly clients referred to rehabilitation centers. Thirteen eight elderly participants in a Rehabilitation Center, Iran, were selected for this study. The samples were randomly assigned to two experimental (n=19) and control (n=19) groups. The study tools are SF-36 quality of life and demographic questionnaires. The questionnaire was collected at baseline, one month, and three after treatment. Descriptive analysis and independent t-test using SPSS (version 22) were used to analyze the data. Results: In the present study, the role of information technology in elderly health programs has been studied. The preliminary analysis demonstrated no statistically significant difference between both groups and some demographic characteristics. Although both groups were comparable at baseline in terms of their quality of life scores (P>0.05), significant differences were found at two-time points after the treatments (P<0.05). Conclusion: The findings of this study demonstrated that the type of information technology use could improve an individual’s quality of life. Suggestions have been made to enhance the role of information technology, to facilitate the provision of services to the elderly, and to inform, provide the necessary warnings and speed up the response to the needs of the elderly.